Problems and Prospects of Agricultural Development and Food Security in Middle Ganga Plain - Siddiqui, Ahmad Mujtaba; Mohammad, Ali; Iqrar, Bushra (National Geographical Journal of India, 2022)
The Middle Ganga Plain experience immense population pressure due to higher growth of population. Due to this phenomenon, many effects are triggered having wider cconomic and environmental implication. The higher population density has put pressure on the cultivated land. Coupled with lower agricultural productivity-an indicator of agricultural backwardness, it creates food insecurity problem. The present paper is an attempt to determine level of agricultural development, understand food self sufficiency and its patterns, and assess the food security. It uses both the primary and secondary data. Effort has also been made to correlate the micro level results with the meso level.